A nature inspired hybrid partitional clustering method based on grey wolf optimization and JAYA algorithm: A NATURE INSPIRED HYBRID PARTITIONAL CLUSTERING METHOD BASED ON GWO AND JAYA ALGORITHM - SHIAL, GYANARANJAN; Sahoo, Sabita; Panigrahi, Sibarama (Computer Science, 2023)
This paper presents a hybrid meta-heuristic algorithm using Grey Wolf optimization (GWO) and JAYA algorithm for data clustering. The idea is use exploitative capability of JAYA algorithm in the explorative phase of GWO to form compact clusters. Here, instead of using one best and one worst solution for generating offspring, three best wolfs and three worst omega wolfs of the population are used. So, the best wolfs and worst omega wolfs assist in moving the new solutions towards the best solutions and simultaneously helps in staying away from the worst solutions. This enhances the chances of reaching the near optimal solutions. The superiority of the proposed method is compared with five promising algorithms, namely GWO, Sine-Cosine Algorithm (SCA), Particle Swarm Optimization (PSO), JAYA and K-means algorithms. The result obtained from the Duncan’s multiple range test and Nemenyi hypothesis based statistical test confirms the superiority and robustness of our proposed method.